الحقوق الإنسانية لأسير الحرب دراسة مقارنة في الفقه الإسلامي واتفاقية جنيف الثالثة الحق في الإيواء والتغذية والكساء أنموذج - محمد الحبيب دشري (University of eloued جامعة الوادي, 2025)
إنّ كثرة الحروب والصراعات الدولية ينتج عنها غالبا فئات ضعيفة تحتاج إلى حماية خاصة، من بينهم أسير الحرب، نتناول في هذه المذكرة الموسومة بـــــــــ ""الحقوق الإنسانية لأسير الحرب_ دراسة مقارنة في الفقه الإسلامي واتفاقية جنيف الثالثة_ الحق في الإيواء والتغذية والكِساء أنموذج""، مع التركيز على ثلاثة حقوق أساسية وهي: الحق في الإيواء، والحق في التغذية، والحق في الكِساء، حيث تطرح المذكرة الإشكالية التالية: كيف عالج كل من الفقه الإسلامي واتفاقية جنيف الثالثة حقوق مأوى وتغذية وكِساء أسير الحرب؟ وأيهما كان أكثر مراعاة لتلك الحقوق؟ كما تهدف هذه الدراسة إلى بيان كيفية تعامل كل من الفقه الإسلامي واتفاقية جنيف الثالثة مع هذه الحقوق نظرياً وتطبيقياً، مع إحداث مقارنة بينهما، وقد اعتمدنا على المناهج التالية: الاستقرائي، الوصفي ثم التحليلي وأخيرا المنهج المقارن، وقد توصلنا في هذه الدراسة إلى أنّه رغم وجود توافق نظري في الاهتمام بحقوق أسير الحرب بين كل من الفقه الإسلامي واتفاقية جنيف الثالثة، إلا أنّ الواقع العملي يشير إلى أنّ الحقوق التي تمت دراستها متوافرة بشكل ثابت في الفقه الإسلامي بينما كانت نادرة الحدوث في تطبيقات اتفاقية جنيف الثالثة، كما نوصي بزيادة نشر الوعي والمعرفة حول حقوق أسير الحرب. The prevalence of wars and international conflicts often results in vulnerable groups that require special protection, among them prisoners of war. In this memorandum, titled 'The Human Rights of Prisoners of War – A Comparative Study in Islamic Jurisprudence and the Third Geneva Convention: The Right to Shelter, Food, and Clothing as a Model,' we focus on three fundamental rights: the right to shelter, the right to food, and the right to clothing, The memorandum raises the following issue: How have both Islamic jurisprudence and the Third Geneva Convention addressed the requirements of shelter, food, and clothing for prisoners of war? Which of the two has been more considerate of these rights? , This study aims to examine how Islamic jurisprudence and the Third Geneva Convention deal with these rights both theoretically and practically, while making a comparison between them. We have relied on the following methodologies: inductive, descriptive, analytical, and comparative, Our study concludes that, despite a theoretical agreement on the importance of prisoners' rights between Islamic jurisprudence and the Third Geneva Convention, practical reality indicates that the rights studied are consistently upheld in Islamic jurisprudence, whereas they are rarely observed in the applications of the Third Geneva Convention, We also recommend increasing awareness and knowledge regarding the rights of prisoners of war.
ماستر شريعة وقانون
Keywords: حقوق; أسير; الإيواء; التغذية; الكساء; Rights; Prisoner; Shelter; Nutrition